Profile of the most prevalent drugs in self-medication in the elderly (Research, Society and Development, 2022)
Self-medication of the elderly is a reality increasingly perceived by studies and by Pharmacy professionals. Many are the elderly who, without adequate information, end up self-medicating. This fact generates several damages to the health of this public. Thus, it is important to know which are the most prevalent drugs used by the elderly, in order to seek solutions to this reality. In view of this scenario, the present study aimed to identify the profile of the drugs most consumed in self-medication in the elderly. In the methodology, an integrative literature review was carried out based on periodical databases, PubMed, Google Scholar and Scielo, whose time frame was between the years 2017 to 2022. In the results, some aspects were found, such as pain relief and malaise are preponderant factors that lead the elderly to self-medicate and analgesics were the most used drugs by this public. In addition, it was also clear to observe the importance of the pharmacist, because it is through him that the incorrect and irrational use of medicines can be prevented, as well as the provision of correct information to the elderly.